Stop Bullying Atas Nama Senioritas - Michela, Michela; Simangunsong, Tresia; Saragih, Hesti Maya Sari; Hutagalung, Ningsih; Hutajulu, Gissa Poala Pratiwi; Ramadhan, Taufiq (CV. Rayyan Dwi Bharata, 2025)
Bullying in the name of seniority has become a critical issue in educational and professional environments. This paper explores how seniority is often misused to justify abusive behavior, resulting in severe mental health impacts on victims, including anxiety, depression, and low self-esteem. Various studies indicate that bullying under the guise of seniority perpetuates a toxic culture of dominance and submission, affecting academic performance and workplace productivity. To address this issue, educators, counselors, and institutional leaders must implement preventive measures and foster a respectful environment. By analyzing existing literature, this paper suggests strategies based on Pancasila values to create a more inclusive and supportive atmosphere. Raising awareness and promoting proactive interventions are essential to stopping bullying in the name of seniority and ensuring a safer, more dignified environment for everyone.